Threatened Preterm Labor: Which are become Preterm Labor? Ancaman Persalinan Preterm: Mana yang menjadi Persalinan Preterm? - Cut M. Yeni; Rismawati Tambunan; Hasanuddin (Indonesian Socety of Obstetrics and Gynecology, 2020)
Objective: The research was aimed to show about characteristics of subject, fetal fibronectin, vaginal pH, cervical length of women with threatened preterm labor, and which are become preterm labor? Preterm labor is occurs most often in 20 weeks gestation to less than 37 weeks gestation. This condition is concerned about Obstetric problem and associated with significant neonatal morbidity and mortality.Methods: This study used the design of case control where preterm pregnant women who become research subjects divided into two groups with threat and without the threat of pre-term labor. Fetal fibronectin , vaginal pHand cervical length than in both groups were evaluated as a risk factor for preterm labor. Mann-Whitney test , Wilcoxon test and Chi-squared test were used as statistical tests with a confidence level of 95%.Results: A total of 86 preterm pregnant women involved in this study with an average age 30 , 5 ± 6.25 (group threat) 32.16 ± 5.25 (non-threatening). Comparison of fetal fibronectin (p = 0.005), vaginal PH(p <0.001) and length of the cervix (p <0.001) between the two groups showed a significant difference. A total of 8 subjects of the 43 in the group of pregnant women with the threat pretem labor experiencing preterm labor .Conclusion: The size of a short cervical length, an increase in the pH of the vaginal secretions and increased levels of fetal fibronectin is a clinical indicator for screening during pregnancy to assess the risk of a preterm labor .Keywords: cervical length, fetal fibronectin, pretermlabor , vaginal pH of the secretions. Abstrak Tujuan: Persalinan preterm adalah persalinan yang terjadi padausia kehamilan 20 hingga kurang dari37 minggu. Kondisi inimerupakanpermasalahan yang sangat mengkhawatirkan dalam bidang kebidanan dan dikaitkan dengan morbiditas dan kematian neonatal yang signifikan. Evaluasi dan skrining terhadap berbagai faktor resiko terjadinya ancaman persalinan preterm adalah hal terpenting dalam mencegah berbagai komplikasi yang mungkin timbul.Metode: Penelitian ini menggunakan desain case control dimana wanita hamil preterm yang menjadi subjek penelitian terbagi menjadi dua yakni kelompok dengan ancaman dan tanpa ancaman persalinan preterm. Fetal fibronectin, pH sekret vagina dan panjang serviks dibandingkan diatara kedua kelompok sebagai faktor resiko ancaman persalinan preterm. Mann-Whitney test, Wilcoxon test dan Chi – squared digunakan sebagai uji statistik dengan tingkat kepercayaan 95%.Hasil: Sebanyak 86 wanita hamil preterm terlibat dalam penelitian ini dengan rerata usia 30,5 ± 6,25 (kelompok ancaman) 32,16 ± 5,25 (tanpa ancaman). Perbandingan Fetal fibronectin (p=0,005), pH sekret vagina (p<0,001) dan panjang serviks (p<0,001) antar kedua kelompok menunjukkan adanya perbedaan yang bermakna. Sebanyak 8 subjek dari 43 pada kelompok wanita hamil pretem dengan ancaman persalinan preterm yang mengalami persalinan pretermKesimpulan:Ukuran panjang serviks yang pendek, peningkatan pH sekret vagina dan peningkatan kadar fetal fibronectin merupakan indikator klinis untuk skrining selama kehamilan guna menilai resiko terjadinya persalinan pretermKata kunci: fetal fibronectin, persalinan preterm, Ph vagina, panjang cerviks